The lund integrated medicines management model, health outcomes and processes development. Issue 2 (12th March 2012) - Eriksson, T.; Bondesson, A.; Holmdahl, L.; Midlov, P.; Hoglund, P.
Abstract : Background: The effects from medication use in clinical trials are hard to achieve in standard care. Instead of health benefits for the patient there is risk of errors and negative consequences such as morbidity, mortality and costs. The risk is highest among older patients admitted and discharged to and from hospital care. Purpose: Develop a systematic model for improved medication use when a patient is admitted to hospital. Materials and methods: Systematic analysis of problems and limitations in the standard patient medication care process from admission, during stay, at, and after discharge was performed at Lund University hospital. A structured team based model with tools, checklists and responsibilities were developed and tested for each part and for the total model. The clinical pharmacist was introduced as the catalyst for improvement in the team and was responsible for performing medication reconciliation and medication review. Each part of the model was researched stepwise and compared to standard care in studies powered to detect significant differences in processes and outcomes. Three of the outcomes studies were used as input in a probabilistic decision tree model for cost-utility analyses. Results: 18 scientific publications and manuscripts have been produced from the development and is the base for four PhD- and more than 30 MSc-theses. The model improves the process of care, that is identifies and solves drug related problem, reduces medication reconciliation errors, and improves medication appropriateness. It also improves healthcare outcomes. Healthcare contacts and hospital readmissions due to medication errors were reduced by 50 percent. For each hour spent by a pharmacist 2-3 h were saved among physicians and nurses. The total model generated savings of €390 and gained utility of 0.005 for each patient. The model is cost saving at a 98% chance. Finally all involved professionals are very satisfied with the process and the pharmacist professional contribution. Conclusions: The model has successfully been implemented, researched and also rewarded as best innovation in Swedish healthcare. In Scania (the south of Sweden) there is a political consensus on the benefit and there are concrete plans to employ 40 additional clinical pharmacists